KOMUNIKASI PEMASARAN OBJEK WISATA SENDANG KUN GERIT DALAM MENINGKATKAN JUMLAH WISATAWAN - Assalami, Ibnu Fajar; Riyanto, Buddy; Muadz, Muadz (Solidaritas, 2024)
The globalization of communications and technology has opened up new opportunities and challenges for the tourism industry in Indonesia. Sendang Kun Gerit is a natural water bathing tourist spot in Sragen Regency which is managed by BUMDES Sumber Rejeki. This tourist attraction achieved significant success with the number of visitors reaching 18 thousand in April 2023. The aim of this research is to describe how marketing communications for the Sendang Kun Gerit tourist attraction can increase the number of visitors. Data was obtained through interviews with the head of management, the publication and marketing section of the Sendang Kun Gerit tourist attraction, and visitors. Apart from that, data is also obtained through observation and documentation. The results of this research show that the use of social media and official websites has an impact on increasing understanding, involvement and persuasion power for potential tourists. Keywords: Marketing Communications, Social Media, Sendang Kun Gerit Sragen